A pet for Petunia - Schmid, Paul. (New York : Harper, 2011)
Petunia so desperately wants a pet skunk that she refuses to believe her parents when they say skunks stink.
1.6
K-3
K-3
Keywords: Parent and child -- Juvenile fiction; Skunks -- Juvenile fiction; Parent and child -- Fiction; Skunks -- Fiction; Parent-child relationship -- Fiction; Skunks -- Fiction; Picture books for children